2018
DOI: 10.3389/fevo.2018.00011
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated Landscapes in Araucaria Forests, Southern Brazil: A Multispecies Local Conservation-by-Use System

Abstract: Araucaria forest is a sub-tropical component of the Atlantic Forest Biome, occurring between 18 and 30 • S latitude, and 500-1,800 m altitude in Southern and Southwestern Brazil and Northwestern Argentina. In recent history (Twentieth century), this forest has undergone non-sustainable exploitation and reduction in area dedicated to agricultural and forestry use. However, smallholders continue using several resources from this forest, even adapting management systems. The main system is geared toward the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 45 publications
0
36
0
1
Order By: Relevance
“…This could take the form of reforestation in resilient areas (though whether other key MOF species would have similar preferred areas in the future is uncertain), or the good stewardship of semi‐natural landscapes in these areas. Some such areas, traditionally managed for cattle or nontimber forest products, can conserve Araucaria's genetic diversity as effectively as protected areas while also providing economic incentives to retain the trees (Medina‐Macedo et al, ; Reis et al, ; Zechini et al, ), so their inclusion in conservation planning is likely to improve Araucaria's climate resilience. However, the legal restrictions on felling mature Araucaria trees (and on land use changes in areas containing them) have led some land owners to actively prevent Araucaria's natural regeneration by removing its seedlings from their properties (Adan et al, ; Mello & Peroni, ; Vibrans et al, ); addressing this issue is critical in order for private lands to contribute effectively to the species' long‐term conservation.…”
Section: Discussionmentioning
confidence: 99%
“…This could take the form of reforestation in resilient areas (though whether other key MOF species would have similar preferred areas in the future is uncertain), or the good stewardship of semi‐natural landscapes in these areas. Some such areas, traditionally managed for cattle or nontimber forest products, can conserve Araucaria's genetic diversity as effectively as protected areas while also providing economic incentives to retain the trees (Medina‐Macedo et al, ; Reis et al, ; Zechini et al, ), so their inclusion in conservation planning is likely to improve Araucaria's climate resilience. However, the legal restrictions on felling mature Araucaria trees (and on land use changes in areas containing them) have led some land owners to actively prevent Araucaria's natural regeneration by removing its seedlings from their properties (Adan et al, ; Mello & Peroni, ; Vibrans et al, ); addressing this issue is critical in order for private lands to contribute effectively to the species' long‐term conservation.…”
Section: Discussionmentioning
confidence: 99%
“…which negatively influence species development, affect the presence of dispersing agents, seasonality and propagule production. In a study that was developed in different landscape units of I. paraguariensis yerba management and cattle grazing, yerba management and no cattle grazing and no management, REIS et al (2018) observed demographic peculiarities between and within the evaluated landscape in the PNC. It is also worth mentioning that microhabitat characteristics can influence the development of individuals that make up a population (RODE et al, 2010), and according to AVILA et al (2016), I. paraguariensis can present a differentiated population structure within the same environment, as well as in the different sampled areas.…”
Section: Population Structurementioning
confidence: 99%
“…Ilex paraguariensis A.St.-Hil (yerba mate) is the most relevant species of its kind from an economic perspective, and it presents a high sociocultural importance for the southern region of Brazil (REIS et al, 2018). It is well known and exploited for its stimulant drink and also for formulating drugs and cosmetics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations